2009
DOI: 10.1088/0953-8984/21/14/145701
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic intermediate coupling superconductivity in Cu0.03TaS2

Abstract: USAEmail: experiment and data analysis: ypsun@issp.ac.cn (Y. P. Sun); theory: zou@theory.issp.ac.cn (L. J. Zou). AbstractThe anisotropic superconducting state properties in Cu 0.03 TaS

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…2 (d), suggesting the intermediate or strong phonon-electron coupling. Figures 3 (a,b) show field dependence of magnetization of Cu 0.05 ZrTe 3 measured at different temperatures for H ⊥ c and H c. For H c, the H c1 is obtained using the demagnetization correction [33]. The H c1 (T) shows almost linear rather than H c1 = H c1 (0)[1-(T/T c ) 2 ] temperature dependence for both field orientations (Fig.…”
Section: Single Crystals Of Cumentioning
confidence: 99%
“…2 (d), suggesting the intermediate or strong phonon-electron coupling. Figures 3 (a,b) show field dependence of magnetization of Cu 0.05 ZrTe 3 measured at different temperatures for H ⊥ c and H c. For H c, the H c1 is obtained using the demagnetization correction [33]. The H c1 (T) shows almost linear rather than H c1 = H c1 (0)[1-(T/T c ) 2 ] temperature dependence for both field orientations (Fig.…”
Section: Single Crystals Of Cumentioning
confidence: 99%
“…The results of angle-resolved photoemission spectroscopy experiments demonstrate that these two orders (CDWs and SC) in the above TMDs may be cooperative phenomena rather than competitive [10,11]. By contrast, it is usually found that the increase of T c is accompanied by the disappearance of CDWs for intercalated 2H-TaS 2 [12][13][14]. The interplay between the superconducting and CDW states has also been investigated by high-pressure experiments on bulk 2H-TaS 2 [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Our former results show that it is a weak pinned superconductor with moderate anisotropy, 9 and that it has a complex vortex phase diagram when H c as HTCS. 10 In order to investigate the vortex motion in Cu 0.03 TaS 2 more thoroughly, we used a special electrodes arrangement (Fig.…”
Section: Introductionmentioning
confidence: 75%